Micro, Small and Medium Enterprises (MSME) Development in Topejawa Beach Tourist Destinations, Takalar Regency Post Covid 19 - Daniel Adolf Ohyver; Agus Syam; Muhammad Jufri; Muhammad Alfa Sikar (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2022)
The coronavirus (COVID-19) outbreak is increasingly spreading and spreading rapidly and is becoming the biggest global polemic for now. It also affects limited SME activity and fewer direct-to-consumer purchases than usual. The development of MSMEs in Topejawa Beach Tourist Destinations, Takalar Regency in the Recovery of the Covid-19 Pandemic, in addition to requiring strategies that can affect the Development of MSMEs in Topejawa Beach Tourist Destinations, Takalar Regency, is a marketing strategy. Based on the background description above, the researcher is interested in conducting research and compiling a thesis, with the title "Analysis of MSME Development in Topejawa Beach Tourist Destinations, Takalar Regency After Covid-19, the problem was formulated in this study, namely Whether Marketing Strategies Affect the Development of MSMEs in Topejawa Beach Tourist Destinations, Takalar Regency in recovering from the Covid-19 Pandemic. Benefits This research is theoretically and beneficially. The population in the number of 63 MSMEs. The sampling method is Purposive sampling samples taken by 63 people for the development of MSMEs at the Topejawa Beach Tourism location, Takalar Regency. something that the questionnaire would measure. Data analysis techniques debgab Conduct validity tests and significance tests of a variable are said to be reliable if they have a Cronbach Alpha > 0.60. In this study, using multiple linear regression analysis using the Statistical Program for Social Science (SPSS) Application Program for windows. This can be seen based on the regression results that have been obtained by researchers, namely T count 13,383 > T table 2,684 with a significance level of 0.002 which means it is smaller than 0.05. Marketing strategy with a Sig rate value of 0.002 < 0.05